1981
DOI: 10.1111/j.1467-1770.1981.tb01375.x
|View full text |Cite
|
Sign up to set email alerts
|

DEVELOPING A MEASURE OF SOCIOCULTURAL COMPETENCE: THE CASE OF APOLOGY1

Abstract: For a number of years, there has been interest in measuring sociocultural competence (Ervin‐Tripp 1972, Hymes 1974, Canale and Swain 1980). This study focuses on one important aspect of such competence: the ability to use the appropriate sociocultural rules of speaking, by reacting in a culturally acceptable way in context and by choosing stylistically appropriate forms for that context. We chose to look at productive performance in sociocultural aspects of speaking, focusing on the speech act of “apology.” Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
183
0
9

Year Published

1984
1984
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(204 citation statements)
references
References 7 publications
12
183
0
9
Order By: Relevance
“…For applied linguists concerned with language acquisition and with intercultur al communicati on, the insights gained through analysis of the social aspects of language use are of particular importance. Recent studies of such speech acts as apologies (Cohen and Olshtain 1981, Olshtain 1983, Olshtain and Cohen 1983, directives (Ervin-Tripp 1976, Blum-Kulka 1982, expressions of disapproval (d'fl.mico-Re isner 1983), and compliments , Wolfson and Manes 198D, Manes 1983, Wolfson 1981) have rich implication s. It has been demonstrated again and again that beneath the surface structure of the linguistic forms and the social etiquette invalved in their use, lies a gold mine of information about the value systems of speakers. In studying apologies, for example, we learn what constitutes an offense, and in studying compliments we learn about what speakers value.…”
Section: University Of Pennsylvani Amentioning
confidence: 99%
See 1 more Smart Citation
“…For applied linguists concerned with language acquisition and with intercultur al communicati on, the insights gained through analysis of the social aspects of language use are of particular importance. Recent studies of such speech acts as apologies (Cohen and Olshtain 1981, Olshtain 1983, Olshtain and Cohen 1983, directives (Ervin-Tripp 1976, Blum-Kulka 1982, expressions of disapproval (d'fl.mico-Re isner 1983), and compliments , Wolfson and Manes 198D, Manes 1983, Wolfson 1981) have rich implication s. It has been demonstrated again and again that beneath the surface structure of the linguistic forms and the social etiquette invalved in their use, lies a gold mine of information about the value systems of speakers. In studying apologies, for example, we learn what constitutes an offense, and in studying compliments we learn about what speakers value.…”
Section: University Of Pennsylvani Amentioning
confidence: 99%
“…For applied linguists concerned with language acquisition and with intercultur al communicati on, the insights gained through analysis of the social aspects of language use are of particular importance. Recent studies of such speech acts as apologies (Cohen and Olshtain 1981, Olshtain 1983, Olshtain and Cohen 1983, directives (Ervin-Tripp 1976, Blum-Kulka 1982 In earlier work on the analysis of complimentin g behavior among middle-clas s Americans (Manes and, it was demonstrate d that there exists a considerabl e (and previously unsuspected) amount of patterning both at the syntactic and the semantic levels. Examination of a corpus of approximate ly seven hundred examples of compliments uttered"in day-to-day interaction s and collected ethnographically , revealed that the spontaneity with which they are often associated is linked more to their freedom of occurrence within an <inter-action than to any originality in structure or lexicon.…”
mentioning
confidence: 99%
“…(Scarcella, 1980;Walters, 1980;Carrell and Konneker, 1981;Cohen and Olshtain, 1981), but such attempts are very scarce in the area of Japaneselanguage teaching.…”
Section: Limitations Of the Study And Suggestions For Further Researchmentioning
confidence: 99%
“…Works that study apology regularly touch on routine/ritualised formulae. Consider Matsumoto (1988), Obeng (1999) and others for examining apology formulae in given languages; Cohen and Olshtain (1981), Olshtain and Cohen (1983), Blum-Kulka and Olshtain (1984), Blum-Kulka et al (1989), Suszczyń ska (1999 or Trosborg (1995) for formulae in cross-cultural apology; Holmes (1990; or Suszczyń ska (2005) for the relation between gender and apology formulae. 4.…”
Section: Notesmentioning
confidence: 99%